Preferential activation of circulating CD8+ and gammadelta T cells in patients with active Behçet's disease and HLA-B51 - Yasuoka, H; Yamaguchi, Y; Mizuki, N; Nishida, T; Kawakami, Y; Kuwana, M (Clinical and experimental rheumatology, 2008)
To evaluate the activation status of circulating CD4+, CD8+, and gammadelta T cells in patients with active and inactive Behçet's disease (BD). We studied 11 subjects with active BD, 28 with inactive BD, and 13 healthy controls. The expression of CD4, CD8, pan-gammadelta, Vdelta1, and Vdelta2 along with the early activation marker CD69 was analyzed by 3-color flow cytometry. Proportions of activated CD8+ and gammadelta T cells were significantly greater in patients with active BD than in those with inactive BD or healthy control subjects, but the proportion of activated CD4+ T cells did not differ among these 3 groups. In addition, significantly greater proportions of the Vdelta1+ and Vdelta2+ gammadelta T-cell subsets were activated in patients with active BD than in those with inactive BD or healthy controls; in active BD, the balance of activation between these subsets favored the Vdelta1+ T cells. No significant differences in these proportions were found between subjects with inactive BD and healthy controls. These findings were observed exclusively in patients with HLA-B51. A comparison of samples from 5 patients taken during active BD and after resolution of BD-related symptoms showed the proportions of activated CD8+ and gammadelta T cells dropped when the patients' BD became inactive. CD8+ and gammadelta T cells, rather than CD4+ T cells, were activated in vivo in patients with active BD and HLA-B51, but not in those with inactive BD, suggesting that these potentially cytotoxic T cells play a critical role in BD flares.